What Parents Think about Higher Secondary Schools in Kerala, India - Sukumar, K. Sreeja; Kumars, Santosh (JOURNAL OF INDIAN EDUCATION, 2017)
An intriguing look deep into the realities of quality of education in Kerala is depressing, even though quantity-wise the progress is astounding, as evidenced through the study reports of NCERT and such other agencies and individual research endeavours. There is a steady flight of students from the mainstream public educational facilities towards private education at extremely higher costs. Are the stakeholders of public education really unsatisfied? Is it not necessary to assess their opinion so that the government recognises the worth of public spending on education? This paper assesses the satisfaction of parents of the students studying in the higher secondary schools in Kerala, on different variables such as: infrastructure, teachers and their attitude, attitude of the principal of the school towards the parents and other supporting system; covering aspects like conduct of parent–teacher meetings, teacher–student ratio, number of working days in a year, permanency of faculty, selection of teachers, counselling for students and parents, career guidance, academic achievements of the school, and importance given to co-curricular and co-academic activities. The opinion of the parents was collected using a pre-tested structured survey schedule constructed based on a five-point Likert-type scale. Percentage analysis and descriptive statistics were computed for identifying the nature of the data. The hypotheses are tested using Z-test, one sample t-test, one way analysis of variance (ANOVA) along with least significant difference test for comparison between more than two groups and independent t-test for comparing between two groups and also correlation. The studies found that the parents are satisfied with the teaching-learning environment of government and government-aided schools but were dissatisfied with the infrastructural facilities.